Combined histological and DNA methylome profiling approaches may provide insights into the pathophysiology of ovarian endometriomas - Ryo Maekawa; Yoshiaki Ota; Ikuko Ota; Yumiko Mihara; Hitomi Takasaki; Shun Sato; Isao Tamura; Yuichiro Shirafuta; Masahiro Shinagawa; Taishi Fujimura; Amon Shiroshita; Toshihide Yoneda; et al. (Reproductive Medicine and Biology, 2023)
Abstract Purpose To test the theory that invaginated ovarian surface epithelium and endometrial implants on the ovary form ovarian endometriomas. Methods Adhesion sites of ovarian endometrioma on the peritoneum and consecutive ovarian endometrioma cyst wall, called non‐adhesion sites, were histologically examined. DNA methylomes of the adhesion sites, non‐adhesion sites, and blueberry spots were compared with those of ovary, endometrium, and peritoneum. Results The non‐adhesion sites showed an ovarian surface epithelium‐like structure near the adhesion site, which continued to a columnar epithelium‐like structure. Calretinin staining was strong in the ovarian surface epithelium‐like structure but weak in the columnar epithelium‐like structure. Estrogen receptors were absent in the ovarian surface epithelium‐like structure, but present in the columnar epithelium‐like structure. The adhesion sites had endometrial gland‐like structures that expressed estrogen receptors. Analyses of DNA methylomes classified the non‐adhesion sites and ovaries into the same group, suggesting that ovarian endometriomas originate from the ovarian surface epithelium. The adhesion sites, blueberry spots and peritoneum were classified in the same group, suggesting that the adhesion sites and blueberry spots originate from the peritoneum. Conclusions The present results support the invagination theory. Ovarian endometriomas consist of invaginated ovarian surface epithelium with celomic metaplasia and endometrium implants on the peritoneum.